1992
DOI: 10.1007/bf00212090
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of methyl isocyanate in rabbit: In vitro and in vivo effects on rabbit erythrocyte membrane

Abstract: Methyl isocyanate (MIC) interaction with the rabbit erythrocyte membrane increased the fluidity of the membrane and decreased the osmotic fragility of erythrocytes both in vitro and in vivo in rabbits intoxicated with MIC subcutaneously. MIC inhibited both acetylcholinesterase (AChE) and adenosine triphosphatase (ATPase) activities of erythrocytes dose-dependently in vitro, while in vivo a decreased trend in ATPase activity with unaltered AChE activity was observed. MIC also caused significant decrease in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…2-Chloroethanediazohydroxide (II), however, is also known to be inactivated through hydrolytic conversion or glutathione (GSH)related metabolism (Figure 1) and has been shown to lead primarily to the excretion of the GSH-related metabolites thiodiacetic acid and thiodiacetic acid sulfoxide in rat urine (10). Reactive isocyanates of CENU's have been suggested to be responsible for undesired toxic side effects of CENU's (11,12), as & consequence of carbamoylation of protein thiols and primary amines of enzymes, such as chymotrypsin (13), adenosine triphosphatase, acetylcholinesterase (AchE) (14), and GSH reductase (15). Several isocyanate-related toxicities have been reported meanwhile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Chloroethanediazohydroxide (II), however, is also known to be inactivated through hydrolytic conversion or glutathione (GSH)related metabolism (Figure 1) and has been shown to lead primarily to the excretion of the GSH-related metabolites thiodiacetic acid and thiodiacetic acid sulfoxide in rat urine (10). Reactive isocyanates of CENU's have been suggested to be responsible for undesired toxic side effects of CENU's (11,12), as & consequence of carbamoylation of protein thiols and primary amines of enzymes, such as chymotrypsin (13), adenosine triphosphatase, acetylcholinesterase (AchE) (14), and GSH reductase (15). Several isocyanate-related toxicities have been reported meanwhile.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanates are known to cause chromosome aberrations, sister chromatid exchanges, mutations, and/ or cancer (16). With methyl isocyanate, distrubed red blood cell membrane functions, alveolar damage which leads to pulmonary edema (14,17,18), and immunotoxicity with concomitant disturbances in pulmonary functions were recently observed in rabbits (19). With n-butyl isocyanate, severe histopathological lesions were observed in rat lungs (20).…”
Section: Introductionmentioning
confidence: 99%
“…MIC can cause hyperglycemia, lactic acidosis, and hypothermia in rats (Jeevaratnam and Vaidyanathan, 1992). Mishra et al (1991) exposed rats to different concentrations of MIC vapor for 8 min and measured drug metabolizing enzymes in lungs and found that aminopyrene demethylase and aniline hydroxylase activities were inhibited, but glutathione-S-transferase activity was increased.…”
Section: Agents That Can Be Used As Weapons Of Mass Destructionmentioning
confidence: 98%
“…2-Chloroethyldiazohydroxides can chloroethylate endogenous nucleophilic sites of macromolecules such as DNA (3). Reactive isocyanates of CENUs have been suggested to cause toxic effects (4,5) by carbamoylation of thiols and primary amines of proteins and enzymes, such as chymotrypsin (6), adenosine triphosphatase, acetylcholinesterase (7) and GSSG-reductase (8). Different isocyanate-related toxicities have meanwhile been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxic effects such as chromosome aberrations, sister chromatid exchanges, mutations and/or cancer are known (9). In rats and rabbits, methyl isocyanate was shown to cause disturbed red blood cell membrane functions, alveolar damage leading to pulmonary oedema (7,10) and immunotoxicity with concomitant disturbances in pulmonary functions (11). With n-butyl isocyanate, severe histopathological lesions were observed in rat lungs (12).…”
Section: Introductionmentioning
confidence: 99%